The Influence of Entrepreneurship Education, Financial Literacy, Love of Money, and Self Efficacy on Entrepreneurial Interest Among Vocational High School Students - Aprilia Riski Andriyani; Mahameru Rosy Rochmatullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of entrepreneurship education, financial literacy, love of money, and self-efficacy on entrepreneurial interest among vocational high school students. A quantitative approach was used with a purposive sampling technique, involving 130 vocational high school students in Indonesia who had received entrepreneurship education. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS. The results showed that entrepreneurship education and love of money had a positive and significant effect on entrepreneurial interest, while financial literacy and self-efficacy did not have a significant effect. These findings confirm that entrepreneurship education enhances students' skills and motivation to become entrepreneurs, while love of money acts as the main driver, indicating that educational factors and financial motivation play an important role in shaping entrepreneurial interest among vocational high school students.